COVID-19 victimization experience and university students’ smartphone addiction: the mediating role of emotional intelligence - Chen, Hongxia; Zhang, Hong-xin (BMC public health, 2023)
Objectives During the post-COVID-19 era, everyone has the risk of contracting the virus and becoming the victims of COVID-19. Examining the relationship between the COVID-19 victimization experience and its effects is more urgent. The aim of present study is to propose a mediation model to investigate the association between COVID-19 victimization experience and smartphone addiction, and the mediating role of emotional intelligence. Methods A online questionnaire including the COVID-19 Victimization Experience Scale, the Smartphone Addiction Scale, and the Emotional Intelligence Scale among Chinese university students, were employed in this study. Finally, 1154 valid questionnaires were collected. The reliability and confirmatory factor analysis results showed that all three scales had good reliability and validity. Results Structural Equation Model (SEM) demonstrated that COVID-19 victimization experience significantly predicted smartphone addiction in university students, and emotional intelligence partially mediated the association between COVID-19 victimization experience and smartphone addiction. Bootstrap results furthermore tested the rigor of the mediating effect. Conclusion COVID-19 victimization experience was a important variables in predicting university students’s martphone addiction, and emotional intelligence was a protective factor in decreasing the negative effect of COVID-19 victimization experience on addictive behaviors. It is suggested that instructors should integrate emotional intelligence training programs into mental health courses so as to improve students’ emotional intelligence ability.